Changes in Aqueductal CSF Stroke Volume and Progression of Symptoms in Patients With Unshunted Idiopathic Normal Pressure Hydrocephalus - Scollato, A.; Tenenbaum, R.; Bahl, G.; Celerini, M.; Salani, B.; Di Lorenzo, N. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Idiopathic normal pressure hydrocephalus (iNPH) represents a diagnostic challenge, given its variable presentation and progression. Stroke volume (SV), defined as the mean volume of CSF passing through the aqueduct during both systole and diastole, greater than or equal to 42 μL, serves as a selection criterion for patients with good probabilities of improvement after ventriculoperitoneal shunt surgery (VPS). In this study, we evaluated the changes in SV during the progression of clinical symptoms in patients with suspected NPH.MATERIALS AND METHODS: Nine patients who presented with clinical and radiologic evidence of NPH, but refused treatment with VPS, were evaluated every 6 months for up to 2 years for progression in their clinical symptoms and changes in their SV, as measured by phase-contrast cine MR imaging (PCCMR).RESULTS: SV seems to increase between the onset of the symptoms and the following 18 to 20 months, then seems to plateau, followed in the next 18 to 20 months by a slight decline, and finally to a more precipitous drop in the next 12 months. During this time, however, the patient’s clinical symptoms progressively worsen.CONCLUSION: Patients with a low SV have not necessarily had brain atrophy and can show, in the following months, a progressive increase in SV, which qualifies them as good candidates for VPS. The progressive reduction of the SV in untreated patients with worsening clinical symptoms may be a sign of a progressive cerebral ischemic injury, which renders the NPH irreversible.